The effect of altitude on the butterfly diversity in the Gunung Gede Pangrango National Park, West Java, Indonesia - Ginoga, Lin Nuriah; Rushayati, Siti Badriyah; Hawari, Inu Fauzan (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Altitude is one of the factors that decrease butterfly diversity due to the different types of habitats. Gunung Gede Pangrango National Park is one of the places at different altitudes, such as Situgunung Resort. This study aimed to investigate butterfly species' diversity, richness, and evenness at three altitude levels. This study was completed in October 2019 at altitudes 750, 850, and 950 meters above sea level (masl). Butterfly inventory (diversity) data were collected using the transect method, and data on habitat characteristics were acquired through direct observation. The richness, diversity, evenness, and community similarity of butterfly species and the biotic and abiotic habitat characteristics were then analyzed. The result showed 51 butterfly species at Situgunung Resort, Gunung Gede Pangrango National Park. The highest diversity index and richness index were found at an altitude of 750 masl (3.22 and 7.91) and the lowest at 950 masl (2.46 and 3.98). The highest evenness index was found at 750 masl, while the highest similarity community index was found at altitudes 750 and 850 masl. The relation between altitude and butterfly diversity is that the higherthe altitude, the lower the butterfly diversity.